2014
DOI: 10.1177/0956462414543121
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of mucocutaneous manifestations in human immunodeficiency virus-infected patients and its correlation with CD4 lymphocyte count

Abstract: In this study, 100 HIV-positive cases (63 men, 37 women) with skin findings were included. The mean CD4 T cell count was 253 cells/mm(3). A total of 235 dermatological manifestations were seen. The common infectious dermatoses were candidiasis (21%), Staphylococcal skin infections (20%), dermatophytoses (14%) and herpes zoster (6%). Among the non-infectious dermatoses were papular pruritic eruptions (20%), xerosis/ichthyosis (20%) and seborrhoeic dermatitis (16%). Statistically significant association (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
6
5
0
1
Order By: Relevance
“…The other skin manifestation that was commonly observed in this study was oral candidiasis. This is the most frequent dermatological manifestation among HIV patients found in many series of studies . It was diagnosed in almost 11.6% of our patients, which is comparable to the study performed by Altuntaş Aydin et al .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The other skin manifestation that was commonly observed in this study was oral candidiasis. This is the most frequent dermatological manifestation among HIV patients found in many series of studies . It was diagnosed in almost 11.6% of our patients, which is comparable to the study performed by Altuntaş Aydin et al .…”
Section: Discussionsupporting
confidence: 91%
“…The pathological relationship between HIV and dermatological conditions begins with seroconversion and intensifies as the CD 4 T cell population is progressively depleted by the virus . This is also supported by other authors who have shown a positive correlation between mucocutaneous manifestations of HIV and low CD 4 T cell counts . Foroughi et al .…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In a study of the spectrum of mucocutaneous manifestations in HIV-infected patients conducted by Fernandes and Bhat a case of verrucous carcinoma of penis was noted. [7] CD4 count in this patient was 31 cells/mm 3 .…”
Section: Discussionmentioning
confidence: 61%